PENGARUH STRATEGI BISNIS TERHADAP KINERJA USAHA KECIL KULINER KEMASAN: SISTEM PENGENDALIAN MANAJEMEN SEBAGAI VARIABEL MODERASI : THE EFFECT OF BUSINESS STRATEGY ON SMALL CULINARY ENTERPRISES PERFORMANCE: MANAGEMENT CONTROL SYSTEM AS A MODERATING VARIABLE - Zaitul, Zaitul; jayanti , Chesren putri; Yasni, Delvi Okti; Wahyuni, Anggela; Rifa, Dandes; Ilona, Desi (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
This study investigates the relationship between business strategy and small culinary enterprise performance. Besides, this study also examines the role of management control systems as moderating variables between business strategy and the performance of small enterprises. Thirty small culinary enterprises are participating in this study. This study uses the primary data collected through a survey. There are three types of variables in this study: dependent variable (performance), independent variables (business strategy) and moderating variables (management control system). Small Enterprise performance has twelve items. Business strategy is divided into two variables: cost leadership strategy and differentiation strategy and these variables have seven items each. Like business strategy, a management control system (MCS) also has two types of variables: diagnostic MCS and interactive MCS. These variables have five items for each. This study uses the structural equation model (SEM-PLS) by applying smart-pls. The result shows that only one hypothesis was accepted: a significant positive relationship between cost leadership strategy and small enterprise performance. Theoretically, this study contributes to the resources-based theory. This finding can be used to improve small enterprise performance by implementing a low-cost strategy